Simulation in thoracic surgery—A mini review of a vital educational tool to maximize peri-operative care and minimize complications - Walji, Hasanali David; Ellis, Steven Aaron; Martin-Ucar, Antonio Eduardo; Hernandez, Luis (Frontiers in Surgery, 2023)
Thoracic surgery is an increasingly expanding field, and the addition of national screening programs has resulted in increasing operative numbers and complexity. Thoracic surgery overall has an approximately 2% mortality and 20% morbidity with common specific complications including persistent air leak, pneumothorax, and fistulas. The nature of the surgery results in complications being unique to thoracic surgery and often very junior members of the surgical team feel underprepared to deal with these complications after very little exposure during their medical school and general surgical rotations. Throughout medicine, simulation is being increasingly used as a method to teach the management of complicated, rare, or significant risk occurrences and has shown significant benefits in learner confidence and outcomes. In this mini review we explain the learning theory and benefits of simulation learning. We also discuss the current state of simulation in thoracic surgery and its potential future in aiding complication management and patient safety.